Nigeria stock market volatility in comparison with some countries: Application of asymmetric GARCH models - Stephen O. Uyaebo; Victor N. Atoi; Farida Usman (CBN Journal of Applied Statistics, 2015)
This study estimated Asymmetric generalized autoregressive conditional heteroscadasticity models with endogenous break dummy on two innovation assumptions using daily all share index of Nigeria, Kenya, United States, Germany, South Africa and China spanning from February 14, 2000 to February 14, 2013. The best fitted models are compared in terms of conditional volatility reaction to market shocks and volatility persistence alongside the asymmetric properties. The results reveal that volatility of Nigeria and Kenya stock returns react to market shock faster than as other countries do. The results also suggest the absence of leverage effect in Nigeria and Kenya stock returns, but confirm its existence in others. In conclusion, the paper suggested that less developed stock markets should improve on market infrastructure, quality of instrument traded on the floor and regulatory practices as such efforts could moderate its fast response to market fluctuations.
Keywords: C22; C52; C53; 330; Stock Market; Volatility; EGARCH; TGARCH; Error Distributions